How often do they meet? Genetic similarity between European populations of a potential disease vector Culex pipiens - Mare Lõhmus; Anders Lindström; Mats Björklund (Infection Ecology & Epidemiology, 2012)
Background: Species in the Culex pipiens complex are common almost all over the world and represent important vectors for many serious zoonotic diseases. Even if, at the moment, many of the pathogens potentially transmitted by Cx. pipiens are not a problem in northern Europe, they may, with increasing temperatures and changing ecosystems caused by climate change, move northward in the future. Therefore, the question whether or not the Cx. pipiens populations in northern Europe will be competent vectors for them is of high importance. One way to estimate the similarity and the rate of contact between European Cx. pipiens populations is to look at the gene exchange between these populations. Methods: To test the genetic diversity and degree of differentiation between European Cx. pipiens populations, we used eight microsatellite markers in 10 mosquito populations originating from northern, central, and southern Europe. Results: We found that three of the analyzed populations were very different from the rest of the populations and they also greatly differed from each other. When these three populations were removed, the variance among the rest of the populations was low, suggesting an extensive historic gene flow between many European Cx. pipiens populations. Conclusions: This suggests that infectious diseases spread by this species may not be associated with a certain vector genotype but rather with suitable environmental conditions. Consequently, we would expect these pathogens to disperse northward with favorable climatic parameters.